Influence of Inspiration to Expiration Ratio on Cyclic Recruitment and Derecruitment of Atelectasis in a Saline Lavage Model of Acute Respiratory Distress Syndrome*. Issue 3 (March 2015) - Boehme, Stefan; Bentley, Alexander H.; Hartmann, Erik K.; Chang, Shi; Erdoes, Gabor; Prinzing, Anatol; Hagmann, Michael; Baumgardner, James E.; Ullrich, Roman; Markstaller, Klaus; David, Matthias
Abstract : Objective: Cyclic recruitment and derecruitment of atelectasis can occur during mechanical ventilation, especially in injured lungs. Experimentally, cyclic recruitment and derecruitment can be quantified by respiration-dependent changes in PaO2 (ΔPaO2 ), reflecting the varying intrapulmonary shunt fraction within the respiratory cycle. This study investigated the effect of inspiration to expiration ratio upon ΔPaO2 and Horowitz index. Design: Prospective randomized study. Setting: Laboratory investigation. Subjects: Piglets, average weight 30 ± 2 kg. Interventions: At respiratory rate 6 breaths/min, end-inspiratory pressure (Pendinsp ) 40 cm H2 O, positive end-expiratory pressure 5 cm H2 O, and FIO2 1.0, measurements were performed at randomly set inspiration to expiration ratios during baseline healthy and mild surfactant depletion injury. Lung damage was titrated by repetitive surfactant washout to induce maximal cyclic recruitment and derecruitment as measured by multifrequency phase fluorimetry. Regional ventilation distribution was evaluated by electrical impedance tomography. Step changes in airway pressure from 5 to 40 cm H2 O and vice versa were performed after lavage to calculate PO2 -based recruitment and derecruitment time constants (TAU). Measurements and Main Results: In baseline healthy, cyclic recruitment and derecruitment could not be provoked, whereas in model acute respiratory distress syndrome, the highest ΔPaO2 were routinely detected at an inspiration to expiration ratio of 1:4 (range, 52–277 torr [6.9–36.9 kPa]). Shorter expiration time reduced cyclic recruitment and derecruitment significantly (158 ± 85 torr [21.1 ± 11.3 kPa] [inspiration to expiration ratio, 1:4]; 25 ± 12 torr [3.3 ± 1.6 kPa] [inspiration to expiration ratio, 4:1]; p < 0.0001), whereas the PaO2 /FIO2 ratio increased (267 ± 50 [inspiration to expiration ratio, 1:4]; 424 ± 53 [inspiration to expiration ratio, 4:1]; p < 0.0001). Correspondingly, regional ventilation redistributed toward dependent lung regions ( p < 0.0001). Recruitment was much faster (TAU: fast 1.6 s [78%]; slow 9.2 s) than derecruitment (TAU: fast 3.1 s [87%]; slow 17.7 s) ( p = 0.0078). Conclusions: Inverse ratio ventilation minimizes cyclic recruitment and derecruitment of atelectasis in an experimental model of surfactant-depleted pigs. Time constants for recruitment and derecruitment, and regional ventilation distribution, reflect these findings and highlight the time dependency of cyclic recruitment and derecruitment. Abstract : Supplemental Digital Content is available in the text.